Innovative Possibilities of Pedagogical Forecasting - Akramovna, Ortiqova Nargiza (European Journal of Life Safety and Stability (2660-9630), 2021)
The scientific article and theoretical significance of the study lies in: determining the content of forecasting as a function of the innovation management process of a higher school teacher closing the management cycle; identification of such features of the implementation of effective forecasting as cyclist (the forecasting procedure should be iterative), multidimensionality (the activity of a higher school teacher is described by a sufficiently large number of parameters) and multilevel forecasting procedure should focus on one of the levels of the hierarchy of management - the activity of the teacher); identification of the main conditions for optimal search forecasting - adaptation of a high school teacher to a modified labor system: complexity (preferred use of a comprehensive forecasting system) and anticipation (working out the forecasting procedure should be carried out throughout the management cycle); disclosure of computer techniques in predicting the activities of a high school teacher: the use of a predictive filter, the use of models of teacher adaptation to a modified labor system.